Case study: Kejora Petshop / Afza Sariff ... [et al.] - Sariff, Afza; Noorhisham, Batrisyia; Razilan, Auni Batrisyia; Azmi, Nur Aida Shahirah; Ab Rahman, Nur Zulaikha; Ahmad Termize, Mizan Maizatul Mayang Puteri (2021)
During the most difficult and chaotic time for businesses to operate, this amazing young lady with the same age with us which is 21 years old is still standing strong on her two feet running a rare business that most people won’t even dare to venture, especially nowadays. Her name is Farah Adibah binti Ahmad Zaifuddin and she runs a pet store as her main source of income. Located at Lot 3072A, Kejora Petshop, Kampung Paya Jaras Hulu, Jalan Haji Karim, 47000 Sungai Buloh, Selangor. Her store offers a variety of services. From selling premium quality pet food for fish, birds and cats to providing pet needs like medication, toys, enclosures, health and even beauty aids. Although her store gravitates towards more on the rural area animals such as unique breeds of roosters and birds. She still can manage to make it as the main focal point of her business later. This case study will discover on how she expands this business and the challenges that she had to face before and during this mass pandemic that has brought a lot of threats to her business. This is a small fragment of her journey on the road of becoming of a soon successful businesswoman.